18F-FDG PET/CT in the Diagnosis and Management of Continuous Flow Left Ventricular Assist Device Infections: A Case Series and Review of the Literature. Issue 2 (March 2018) - Akin, Sakir; Muslem, Rahat; Constantinescu, Alina A.; Manintveld, Olivier C.; Birim, Ozcan; Brugts, Jasper J.; Maat, Alexander P.W.M.; Fröberg, Alida C.; Bogers, Ad J.J.C.; Caliskan, Kadir
Abstract : Implantable continuous flow left ventricular assist devices (LVADs) are increasingly used in end-stage heart failure treatment as a bridge-to-transplant and destination therapy (DT). However, LVADs still have major drawbacks, such as infections that can cause morbidity and mortality. Unfortunately, appropriate diagnosis of LVAD-related and LVAD-specific infections can be very cumbersome. The differentiation between deep and superficial infections is crucial in clinical decision-making. Despite a decade of experience in using fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) to diagnose various infections, its use in LVAD patients remains scarce. In this case series, we review the current evidence in literature and describe our single center experience using 18 F-FDG PET/CT for the diagnosis and management of LVAD infections. Abstract : Supplemental Digital Content is available in the text.